The Effect of Cigarette Smoking on Solubility and Disintegration of Resin Modified Glass Ionomer Cement - An In Vitro Study - merin mathew; AbdulrahmanSaad L Alanzi; ThaniFarhan O Alruwaili (Mashhad University of Medical Sciences, 2020)
Introduction: Glass ionomer cement (GIC) is a dental restorative material that is prone to solubility and degradation. GIC could degrade in presence of water and desiccation due to environmental factors during setting process and eventually might lead to the failure of the restoration. Cigarette smoking brings a complex chemical mixture to oral cavity that can inhibit polymerization and promote the solubility of this cement. Therefore, the aim of this study was to evaluate the effect of cigarette smoking on solubility and disintegration of resin-modified glass ionomer cement (RMGIC). Methods: RMGIC used for preparation of control group (n=54) with same number of samples in test group (n=54). The test groups were exposed to cigarette smoking. Samples divided in groups of 6 to immerse in three different mediums (water, normal saline and qahwa, the Arabic tea) for the immersion periods of 1h, 24h and 7days. Differences in weight of each sample were recorded before and after immersion. One Way Anova followed by Tukey- Kramer multiple comparison test was used to analyze data. Results: Test group exhibited significant dissolution irrespective to the type of medium or duration of immersion. Therefore, exposure to direct or indirect cigarette smoking within the first hour of the setting time of RMGIC cause dissolution of it. In addition, consumption of qahwa, within one hour of cement placement causes initial dissolution in both control and test groups. Conclusion: Cigarette smoke exposure and consumption of qahwa drink within the initial hour of cement placement is not recommended.